Bioprospecting North Atlantic microalgae with fast growth and high polyunsaturated fatty acid (PUFA) content for microalgae-based technologies - Steinrücken, Pia; Erga, Svein Rune; Mjøs, Svein Are; Kleivdal, Hans Torstein; Prestegard, Siv Kristin (Algal Research, 2017)
Microalgae are considered to be an important and sustainable alternative to fish oil as a source for the polyunsaturated fatty acids (PUFAs) eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). Due to their health benefits, there is an increasing interest in the commercial application of these fatty acids (FA) to health and dietary products, and to aquaculture feeds. However, FA from microalgae are still expensive to produce compared to fish or plant oils. With only a few microalgal strains being cultivated on a large scale for commercial PUFA production, prospecting for new, robust and fast-growing strains with increased PUFA content is essential in order to reduce production costs. Microalgae from northern high latitudes, exposed to cold temperatures, may be especially promising candidates as previous studies have shown increasing unsaturation of FA in response to decreasing growth temperatures in different microalgae, most likely to maintain membrane fluidity and function. We have designed a screening pipeline, targeting a focused search and selection for marine microalgal strains from extreme North Atlantic locations with high robustness and biomass production, and increased levels of EPA and DHA. The pipeline includes a rational sampling plan, isolation and cultivation of clonal strains, followed by a batch growth experiment designed to obtain information on robustness, growth characteristics, and the FA content of selected isolates during both nutrient replete exponential cultivation and nutrient limited stationary cultivation. A number of clonal cultures (N = 149) have been established, and twenty of these strains have been screened for growth and FA content and composition. Among those strains, three showed growth rates ≥ 0.7 d− 1 at temperatures of 15 °C or below, and high amounts of EPA (> 3% DW), suggesting their potential as candidates for large scale production. publishedVersion